Assessment of Hepatic Mineral Composition in Sheep, Cattle, Chicken, and Fish in Erbil City, Kurdistan Region-Iraq - Hussein, Abdulqader Ahmed; Omer, Samad S.; Ali, Iman S.; Suleiman, Bnar F. (Kurdistan Journal of Applied Research, 2021)
Liver mineral concentrations of 232 samples from slaughtered animals, including lamb, yearling, sheep, and cattle, checkin, and fish were detrmined, using X-ray fluorescence spectrometer, to provide data regarding to the liver mineral concentrations (mg/kg dry weight). The mean liver Zn and Co liver conentrations of lambs (286, 1.9), yearling (233, 1.7), sheep (254, 1.8), and cattle (276, 1.8) in majority samples were adequate, while liver Pb concentrations of mentioned animals (45.3, 48.1, 46.4, 39.6) mg/kg respectively were high and exceeded toxic levels. In checkin, the mean liver Cu, Zn, and Co were also adequate, with the mean values of (26.4), (298.8), and (1.8) mg/kg respectively. Though, the mean liver Fe concentration (2257.0 mg/kg) was high, and liver Pb concentration (6.2 mg/kg) was reched toxic level. In fish, for majority liver samples, the mean concentration of Cu (191.8), Fe (6800.0), Zn (202.8), Co (3.3), Pb (8.6), and Ni (6.3) were high and toxic. In conclusion, liver Pb (and Ni only in fish) concentration in all studied animals for the majority of examined sample were higher than normal and toxic. Wherese, other studied minerals in majority of liver samples were adequate. Therefore, it can be concluded that there are problems on animal and human health (due to high concentration of Pb and Ni) would be raised at present from the consumption of ovine, bovine, checkin, and fish slaughtered from the city of Erbil.